Monometallic and heterobimetallic ruthenium (II) and palladium (II) complexes based on a pyridine-hydrazone ligand as bifunctional catalysts for ROMP of norbornene and ethylene polymerization - Gois, Patrik Dione de Santana [UNESP]; Maia, Juliana Iris Pereira; Masson, Gustavo Henrique Cicero [UNESP]; Martins, Daniele Maria; Machado, Antonio Eduardo da Hora; Goi, Beatriz Eleutério [UNESP]; Maia, Pedro Ivo da Silva; Carvalho-Jr, Valdemiro Pereira de [UNESP] (Wiley, 2022)
The monometallic complex [Pd(L)(PPh3)] (mono-Pd) was synthesized using a potentially tridentate hydrazone (H2L) and used as precursor to prepare a heterobimetallic ruthenium (II)-palladium (II) complex [Cl2(p-cymene)Ru(μ-L)Pd (PPh3)] (Ru-Pd). Mono-Pd and Ru-Pd were characterized by fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV–Vis), 1H, 13C{1H} and 31P{1H} nuclear magnetic ressonance(NMR) spectroscopy, elemental analysis, cyclic voltammetry, matrix-assisted laser desorption/ionization - time of flight (MALDI-TOF) mass spectrometry, and computational methods. The mono-Pd was additionally studied by single-crystal X-ray diffraction. The complex [RuCl2(p-cymene)(Isoniazid)] (mono-Ru) was also obtained following literature methods aiming a comparison in the catalytic activity. The ring opening metathesis polymerization (ROMP) of norbornene (NBE) using mono-Ru or Ru-Pd as precatalysts in the presence of ethyl diazoacetate (EDA) was evaluated as a function of time (10–60 min) using [NBE]/[EDA]/[Ru] = 5000/28/1 at 50°C. The time increases produced good yields of polyNBE, reaching 38% and 46% for mono-Ru and Ru-Pd, respectively. The polyNBE produced was measured by size-exclusion chromatography (SEC) and reached an order of magnitude of 105 g·mol−1 of Mn, with Ð values ranging from 2.51 to 1.86 for mono-Ru and from 3.50 to 1.66 for Ru-Pd. The catalytic activity of mono-Pd and Ru-Pd on ethylene polymerization was assessed with a range of [Al]/[Pd] molar ratio between 350 and 1750, 30–70°C temperature, 2 to 4 h reaction time, and total reaction volume of 25 and 50 ml. Mono-Pd achieved an activity of 22.80 kg PE (mol Pd)−1 h−1 at 60°C after 4 h using [Al]/[Pd] = 1050, 7 μmol of catalyst in 25 ml of toluene, and 116 psi ethylene. For Ru-Pd, an activity of 20.35 kg PE (mol Pd)−1 h−1 at 60°C after 4 h was obtained using [Al]/[Pd] = 1750, 7 μmol of catalyst in 25 ml of toluene, and 116 psi ethylene. Overall, Ru-Pd showed to be active in both ROMP and ethylene polymerization reactions, being categorized as a bifunctional catalyst.